(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2025)
Materials and methods: herbarium collections, literature data, field observations. Nomenclature: POWO 2025, Euro+Med Plant Base 2025, Hassler 1994–2025. Results: In the flora of Ukraine, the Salicaceae family is represented by two genera: Populus and Salix. The genus Populus includes 4 autochthonous species (one of which is hybridogenic) and 8 frequently cultivated species (two of which are hybridogenic). In addition, many other species and forms are cultivated in botanical gardens and arboretums. A synonym of P. alba, which varies greatly in the size and shape of the leaves, is the name P. bolleana, which was previously used to denote a separate species. The name P. candicans is a synonym of P. balsamifera, which is widely cultivated in most of the country, mainly in the forest-steppe and steppe, and often goes wild. Populus canadensis is given under two names for Ukraine: P. canadensis and as P. deltoides (the latter does not grow in Ukraine). The genus Salix in Ukraine is represented by 23 autochthonous species and many hybrid forms are also known. The growth of such species as: S. hastata (for the Carpathians), S. reticulata (for the Carpathians), S. repens (for the western regions) has not been confirmed in Ukraine. There is not a single authentic specimen of these species in the herbariums of Ukraine. All data on the growth of S. repens in Ukraine actually refer to S. rosmarinofolia, from which S. repens differs in having wider lanceolate or elliptic leaves, with a curved apex and curved edges, and short cylindrical carpels. Until now, the growth of S. xerophila in Ukraine has not been confirmed, the name of which according to modern nomenclature is considered a synonym of S. bebbiana. This is a species with a wide discontinuous range, which covers North America, North-Eastern Europe, Western Siberia and South-Eastern Asia and does not enter Ukraine. There are also many nomen¬clatural changes in the genus Salix. In particular, a synonym of the typical S. babylonica is the name S. matsudana, which was previously erroneously recognized as a separate species with smaller leaves. The names S. × elegantissima and S. × blanda are synonyms of the typical nothoform S. × pendulina nothof. pendulina, which is widely cultivated in Ukraine. The species S. rhaetica for Ukraine (Carpathians) was given by mistake, instead of S. phylicifolia. Many other species and hybrid forms of the genus Salix are also cultivated in Ukraine. Analysis of literature data shows that the replacement of the species name S. fragilis with S. euxina, as well as the replacement of the name of the hybrid S. rubens (S. alba × S. fragilis) with S. × fragilis (S. alba × S. euxina) are incorrect and should be rejected.